Pengaruh Pemupukan Organik, Semi Organik dan Anorganik terhadap Sifat Fisika, Kimia Tanah dan Hasil Padi Pada Beberapa Munduk Di Subak Mambal - DEWA AYU PUTU RISTA SWANDEWI; NI MADE TRIGUNASIH; A.A. NYOMAN SUPADMA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
The Influence of Organic, Semi Organic and Anorganic Fertilization on Physical, Chemical soil Characteristic and Rice Yield in Some Munduk in Subak Mambal Rice is a major requirement for the people in Indonesia. The decrease of soil fertility which resulted in optimal rice productivity in paddy fields, due to low fertilizer efficiency. Soil fertility needs to be improved through proper and balanced fertilization. This research aims knowing the effect of organic, semi-organic and anorganic fertilization on some Munduks in Subak Mambal, on physical properties, chemical soil and rice yield.This research used Nested Design. The treatment consists of three types of fertilization are organic fertilization, semi-organic fertilizer and anorganic fertilization. The location treatment consists of four Munduk are Munduk Batuangsut location, Munduk Kedampal location, Munduk Bedugul location and Munduk Semana location.The result of statistical analysis showed that organic fertilizer, semi-organic and anorganic treatments had significant effect (P <0,05) to very real (P <0,01) on all parameters observed except the bulk density and soil pH. The organic fertilizer treatment at the Munduk Batuangsut location gave the highest rice yield average of 8,0 tons ha-1, at the location of Munduk Kedampal gave the highest rice yield average of 7,32 tons ha-1. The semi-organic fertilizer treatment at the location of Munduk Bedugul gave the highest rice yield average of 7,8 tons ha-1 and at the location of Munduk Semana gave the highest average yield of 7,5 tons ha-1.